GE_GERICHTE P/2726/2021 vom 27. August 2021 - GE Cour de justice (2021)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;LÉSION CORPORELLE SIMPLE;VOIES DE FAIT;MENACE(EN GÉNÉRAL) | CPP.310.al1.leta; CP.123; CP.126; CP.180